Modeling and Analysis of Process Factors’ Effect on Performance in Crude Palm Oil Processing Time: A Simulation-Based Approach - JOHN, ANAK INYANG; Magdalene, Andrew Munot (UNIMAS, 2024)
Crude Palm Oil (CPO) industry has emerged as one of the main agricultural commodities and contributes significantly to the national economy. Studies showed process factors such as fresh fruit bunches (FFBs), workers, process, machines and components and working method affect the performance of a CPO production system. However, there is no study that investigate the performance of CPO production system considering these process factors and the possibility of interactions between these process factors. The first objective is to develop a simulation model of CPO production. Second, to analyse the process factors and simulated processing times using ANOVA to identify significant factors and interactions between factors. Third, to propose managerial strategies to reduce the processing time. The research tools used are discrete event simulation (DES), design of experiment (DOE) and analysis of variance (ANOVA). Four industrial cases are considered; for Case A & Case B the simulated operation time are 8 hours and 16 hours, respectively. While for Case C & D the simulated FFBs quantity are 250 metric tonnes and 1250 metric tonnes, respectively. For Case A & B findings showed process factors such as FFBs quantity, FFBs inter-arrival time and tipping machine repair time are significant. Also, for Case A & B, the interaction between FFBs quantity and inter-arrival time is significant. For Case C & D, tipping machine repair time and weighbridge machine repair time are significant. For Case C, there is no significant interaction between factors, while for Case D, the interaction between weighing time and weighbridge repair time is significant. In sum, availabilities of FFBs quantity and tipping machine are crucial to achieve short processing time. Thus, management of palm oil mill must implement strategies to sustain availabilities of FFBs and tipping machine.